2017
DOI: 10.1371/journal.pone.0169991
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Enhanced Transgenic Coho Salmon (Oncorhynchus kisutch) Strains Have Varied Success in Simulated Streams: Implications for Risk Assessment

Abstract: Growth hormone (GH) transgenic fish have accelerated growth and could improve production efficiency in aquaculture. However, concern exists regarding potential environmental risks of GH transgenic fish should they escape rearing facilities. While environmental effects have been examined in some GH transgenic models, there is a lack of information on whether effects differ among different constructs or strains of transgenic fish. We compared growth and survival of wild-type coho salmon (Oncorhynchus kisutch) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Growth outcomes of GH treatment were context-dependent as we found that they differed between the hatchery conditions and the experimental streams. They are likely a result of a trade-off between energy returns and costs of food acquisition, which differs between hatchery and natural conditions (Leggatt et al, 2017;Sundström et al, 2007b). This is consistent with previous studies showing that growth outcomes tend to decrease as environmental complexity increases and food availability decreases (Leggatt et al, 2017;Sundström et al, 2007b;Sundt-Hansen et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Growth outcomes of GH treatment were context-dependent as we found that they differed between the hatchery conditions and the experimental streams. They are likely a result of a trade-off between energy returns and costs of food acquisition, which differs between hatchery and natural conditions (Leggatt et al, 2017;Sundström et al, 2007b). This is consistent with previous studies showing that growth outcomes tend to decrease as environmental complexity increases and food availability decreases (Leggatt et al, 2017;Sundström et al, 2007b;Sundt-Hansen et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Ratios of survival and growth are given relative to wild-type fish, red fill indicates indices significantly greater in T fish, and green fill indicates indices significantly greater in W fish. * indicates data is from current study, and superscripts indicate where data is from previously published studies: a 27 ; b 26 ; c 29 ; d 13 ; e 23 ; f 21 ; g 25 .…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that relative survival of fast- and slow-growing strains can vary (including reverse) depending on the environment, but the specific environmental characteristics driving these trends and uncertainties are not fully known. Some factors identified to reverse relative growth and survival trends of transgenic and wild-type strains include prior rearing conditions 26 and interactions among food level and presence or timing of predator exposure 23,29 . Better understanding of the relative role and impact of different environmental characteristics will help to reduce the uncertainty involved with ecological risk assessments.…”
Section: Introductionmentioning
confidence: 99%